Buffalo Paper - The Geology of Buffalo as Related to Natural-Gas Explorations along the Niagara River - Charles Albert Ashburner (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1889)
THE stratigraphical geology of the vicinity of Buffalo has always been of great interest on account of its bearing on the origin and history of the Niagara-river gorge, between the Falls and Lake Ontario. Recently, however, the character and thickness of the strata which underlie Buffalo have acquired more practical and economic importance on account of their relation to the possible occurrence of natural gas in commercial quantity near the Niagara river. In a paper presented at the Duluth meeting (l887), on " Petroleum and Natural Gas in New york State" (Trans., xvi., 906), I gave a brief description of the four wells which had been drilled by the Buffalo Cement Company between 1883 and that time. One of these wells is 1305 fret deep; and, at the time that my paper was finally revised for the Transactions (June, 1888), it was still an open question whether the drill in this well had reached the Niagara limestone, or had penetrated the Medina sandstones and shales, which latter are boldly exposed in a number of localities in the district, hut more particularly along the Niagara river in the vicinity of Lewiston and Qneenstown. The difficulty in this geological question at Buffalo has lain in the fact that no reliable determination could be made of the thickness of the strata included between the Corniferous limestone, immediately below which the drilling of the Buffalo gas-wells was commenced, and the Niagara limestone. On the other hand, the strata included between the latter limestone and the middle portion of the Medina sandstones and shales, have been minutely measured and studied in the Niagara gorge below the Falls by many American and European geologists. The first reliable section of these strata was constructed by Professor Eaton, and published in 1824 in his report on the Geological and Agricultural Survey of the District adjoining the Erie Canal. This section, extending from Lake Erie to Lewiston, is complete, with the exception that no thickness is given to the Salina or Onoudaga salt group,